The Association Between Broad Antigen HLA Mismatches, Eplet HLA Mismatches and Acute Rejection After Kidney Transplantation. Issue 12 (December 2016) - Do Nguyen, Hung Thanh; Wong, Germaine; Chapman, Jeremy R.; McDonald, Stephen P.; Coates, Patrick T.; Watson, Narelle; Russ, Graeme R.; D'Orsogna, Lloyd; Lim, Wai Hon
Abstract : Background: Epitope matching, which evaluates mismatched amino acids within antigen-antibody interaction sites (eplets), may better predict acute rejection than broad antigen matching alone. We aimed to determine the association between eplet mismatches and acute rejection in kidney transplant recipients. Methods: The association between eplet mismatches, broad antigen mismatches and acute rejection was assessed using adjusted Cox proportional hazard regression. Model discrimination for acute rejection was evaluated using the area under receiver operating characteristic curves. Results: Of the 3, 499 kidney transplant recipients from 2006 to 2011, the average (SD) number of broad antigen and eplet mismatches were 3.4 (1.7) and 22.8 (12.2), respectively. Compared with 0 to 2 eplet mismatches, the adjusted hazard ratio (HR) for acute rejection among those with 20 or greater eplet mismatches was 2.16 (95% confidence interval [CI], 1.33-3.52; P = 0.001). The adjusted area under the curve for broad antigen mismatches was 0.58 (95% CI, 0.56-0.61), similar to that for eplet mismatches (HR, 0.59; 95% CI, 0.56-0.61; P = 0.365). In recipients who were considered as low immunological risk (0-2 broad antigen HLA-ABDR mismatch), those with 20 or greater eplet mismatches experienced an increased risk of rejection compared to those with less than 20 mismatches (adjusted HR, 1.85; 95% CI, 1.11-3.08; P = 0.019). Conclusions: Increasing number of eplet mismatches is associated with acute rejection in kidney transplant recipients. Consideration of eplet HLA mismatches may improve risk stratification for acute rejection in a selected group of kidney transplant candidates. Abstract : Supplemental digital content is available in the text.